EVALUATION OF TRENDS IN ONCOLOGICAL CARE FOR KIDNEY CANCER IN KAZAKHSTAN - Dyakov, S.; Telmanova, Zh; Bilalova, Z.; Azhetova, Zh; Igissinova, G.; Orozbaev, S.; Kudaibergenova, I.; Igissinov, N. (Oncologia i radiologia Kazakhstana, 2022)
Relevance: Worldwide, kidney cancer (KC) ranks sixth among the most frequently diagnosed cancers in men and 10th in women, accounting for 5% and 3% of all cancer diagnoses, respectively. In 2020, IARC reported 431,288 new cases and 179,368 deaths from KC worldwide. By 2040, they expect an increase of 40.4% in KC incidence (605,726 cases) and 59.4% in KC mortality (285,906 deaths). The aim was to analyze some kidney cancer indicators (incidence, mortality, early diagnosis, neglect, morphological verification) to evaluate the oncological care in Kazakhstan in 2010-2019. 25. Ahmad O.E., Boschi-Pinto C., Lopez A.D., Murray C.J.L., Lozano R., Inoue M. Age standardization of rates: a new WHO standard. – GPE Discussion Paper Series: No.31. – EIP/GPE/EBD World Health Organization, 2001. https://cdn.who.int/media/docs/defaultsource/gho-documents/global-health-estimates/gpe_discussion_ paper_series_paper31_2001_age_standardization_rates.pdf. 21.11.2022 26. Мерков А.М., Поляков Л.Е. Санитарная статистика. – Ленинград: Медицина, 1974 г. – 384 с. [Merkov A.M., Polyakov L.E. Sanitarnaya statistika. – Leningrad: Medicina, 1974 g. – 384 s. (in Russ.)]. 27. Гланц C. Медико-биологическая статистика. Пер. с англ. — М.: Практика, 1998. – 459 с. 28. Расчет t-критерия Стьюдента при сравнении средних величин (онлайн калькулятор) [Raschet t-kriteriya St’yudenta pri sravnenii srednix velichin (onlajn kal’kulyator) (in Russ.)] // medstatistic. ru/calculators/averagestudent.html. 21.11.2022 29. Закон Республики Казахстан. О государственной статистике: утв. 19 марта 2010 года, № 257-IV [Zakon Respubliki Kazaxstan. O gosudarstvennoj statistike: utv. 19 marta 2010 goda, № 257-IV (in Russ.)] // http://adilet.zan.kz/rus/docs/Z100000257 30. WMA Declaration of Helsinki – Ethical Principles for Medical Research Involving Human Subjects. – 2013. . 21.11.2022. 31. Alkhateeb S.S., Alkhateeb J.M., Alrashidi E.A. Increasing trends in kidney cancer over the last 2 decades in Saudi Arabia // Saudi Med J. – 2015. – Vol. 36. – P. 698-703. https://doi.org/10.15537/smj.2015.6.10841 32. Arabsalmani M., Mohammadian-Hafshejani A., Ghoncheh M., Hadadian F., Towhidi F., Vafaee K., Salehiniya H. Incidence and mortality of kidney cancers, and human development index in Asia; a matter of concern // J. Nephropathol. – 2016. – Vol. 6. – P. 30-42. https://doi. org/10.15171/jnp.2017.06 33. Thorstenson A., Bergman M., Scherman-Plogell A.H., Hosseinnia S., Ljungberg B., Adolfsson J., Lundstam S. Tumour characteristics and surgical treatment of renal cell carcinoma in Sweden 2005-2010: a population-based study from the national Swedish kidney cancer register // Scand. J. Urol. – 2014. – Vol. 48. – P. 231-238. https://doi.org/10.3109/21 681805.2013.864698 ОРГАНИЗАЦИЯ ЗДРАВООХРАНЕНИЯ Онкология и радиология Казахстана, №4 (66) 2022 9 Прозрачность исследования: Авторы несут полную ответственность за содержание данной статьи. Конфликт интересов: Авторы заявляют об отсутствии конфликта интересов. Финансирование: Авторы заявляют об отсутствии финансирования исследования. Вклад авторов: вклад в концепцию – Кудайбергенова И.О., Игисинов Н.С., Дьяков С.С.; научный дизайн – Билялова З.А., Игисинова Г.С., Дьяков С.С.; исполнение заявленного научного исследования – Орозбаев С.Т., Дьяков С.С.; интерпретация заявленного научного исследования – Ажетова Ж.Р., Дьяков С.С., Тельманова Ж.Б.; создание научной статьи – Дьяков С.С., Тельманова Ж.Б. Сведения об авторах: Дьяков Сергей Сергеевич – науч. сотр. ОО «Central Asian Institute for Medical Research», Астана, Республика Казахстан; аспирант ГУ «Кыргызской государственной медицинской академии им. Ахунбаева», Бишкек, Кыргызская Республика; врач лучевой диагностики в РГП на ПХВ «Национальном научном Центре Травматологии и Ортопедии им. Акад. Н.Д. Батпенова МЗ РК», Астана, Республика Казахстан, тел. +77024622269, e-mail: sergey_djakov@mail.ru, ID ORCID: https://orcid.org/0000-0001-7566-7094; Тельманова Жансая Бекмакановна – науч. сотр. ОО «Central Asian Institute for Medical Research», Астана, Республика Казахстан; науч. сотр. ОО «Eurasian Institute for Cancer Research», Бишкек, Кыргызская Республика; интерн 7-го курса факультета общей врачебной практики НАО «Медицинский университет Астана», Астана, Республика Казахстан, тел. +77075059398, e-mail: telmanova.zhansaya@gmail.com, ID ORCID: https://orcid.org/0000-0002-2364-6520; Билялова Зарина Ароновна – PhD, асс. проф., гл. науч. сотр. ОО «Central Asian Institute for Medical Research», Астана, Республика Казахстан; ст. науч. сотр. ОО «Eurasian Institute for Cancer Research», Бишкек, Кыргызская Республика, тел. +77051464888,e-mail: z.bilyalova@gmail.com, ID ORCID: https://orcid.org/0000-0002-0066-235X; Ажетова Жанерке Рахимбаевна – доц. каф. акушерства и гинекологии, НАО «Медицинский университет Астана», Астана, Республика Казахстан; науч. сотр. ОО «Central Asian Institute for Medical Research», Астана, Республика Казахстан, тел. +77017398009, e-mail: azhetova@mail.ru, ID ORCID: https://orcid.org/0000-0002-8266-1720; Игисинова Гульнур Сагинбековна – к.м.н., доц. каф. онкологии, НАО «КазНМУ им. Асфендиярова», Алматы, Республика Казахстан; Учредитель и председатель ОО «Central Asian Institute for Medical Research», Астана, Республика Казахстан, e-mail: gulnurs@list.ru, ID ORCID: https://orcid.org/0000-0001-6881-2257; Орозбаев Серикбай Тлеугабылович – к.м.н., доц. каф. хирургических болезней с курсами кардиоторакальной хирургии и ЧЛХ, НАО «Медицинский университет Астана», Астана, Республика Казахстан, науч. сотр. ОО «Central Asian Institute for Medical Research», Астана, Республика Казахстан, тел. +77015339881, e-mail: orazbaev_s.t@mail.ru, ID ORCID: https://orcid.org/0000-0003-3895-0426; Кудайбергенова Индира Орозбаевна – д.м.н., проф., Ректор ГУ «Кыргызской государственной медицинской академии им. Ахунбаева», Бишкек, Кыргызская Республика; гл. науч. сотр. ОО «Eurasian Institute for Cancer Research», Бишкек, Кыргызская Республика, тел. +0(312)540495, e-mail: k_i_o2403@mail.ru, ID ORCID: https://orcid.org/0000-0003-3007-8127; Игисинов Нурбек Сагинбекович (корреспондирующий автор) – д.м.н., проф., рук. ОО «Central Asian Institute for Medical Research», Астана, Республика Казахстан; проф. каф. хирургических болезней с курсами кардиоторакальной хирургии и ЧЛХ, НАО «Медицинский университет Астана», Астана, Республика Казахстан; Учредитель и председатель ОО «Eurasian Institute for Cancer Research», Бишкек, Кыргызская Республика; проф. каф. менеджмента научных исследований, ГУ «Кыргызская государственная медицинская академия им. Ахунбаева», Бишкек, Кыргызская Республика; НАО «Медицинский университет Астана», Астана, 010000, ул. Бейбитшилик, 49а, Республика Казахстан, тел. +77024293421, e-mail: n.igissinov@gmail.com, ID ORCID: https://orcid.org/0000-0002-2517-6315. Methods: The material of the study was the data of the Ministry of Health of the Republic of Kazakhstan – annual Form No. 7 and 35 concerning KC (ICD 10 – C64) for 2010-2019 – incidence, mortality, early diagnosis, neglect, morphological verification. A retrospective study using descriptive and analytical methods of biomedical statistics was used as the main method. Results: From 2010 to 2019, 10,966 new cases of KC and 3,866 deaths from this pathology were registered in Kazakhstan. KC incidence increased from 5.9±0.2%⁰⁰⁰ (2010) to 6.7±0.2%⁰⁰⁰ in 2019 (p=0.000). In dynamics, mortality rates from KC tended to decrease from 2.6±0.1%⁰⁰⁰ (2010) to 1.8±0.1%⁰⁰⁰ in 2019 (p=0.000). The study reveals a trend: the indicators of early diagnosis (the proportion of patients with stage I-II) improved from 50.7% (2010) to 69.1% in 2019, and, accordingly, the proportion of neglected patients decreased significantly with stage III (from 31.2% to 14.6%) and with stage IV (from 18.1% to 16.0%). Morphological verification indicators for KС improved by 44.7%, from 58.5% and 84.6%, respectively, in 2010 and 2019. Conclusion: The increase in KC incidence dictates further study of cause-and-effect relationships with risk factors to develop effective preventive measures and screening programs.